Seismic behaviour of interior reinforced-concrete beam–column sub-assemblages with engineered cementitious composites - Lee, Siong Wee (2018)
The feasibility of using engineered cementitious composites (ECC) in joint cores of reinforced-concrete (RC) beam–column sub-assemblages as a means to enhance seismic behaviour is evaluated. Four RC beam–column sub-assemblages are constructed and tested under lateral cyclic loading. One RC beam–column sub-assemblage with normal concrete in the joint and one RC sub-assemblage with ECC in the joint are designed to gravity loads; neither type has transverse reinforcement in the joint core. Similarly, one RC sub-assemblage with normal concrete in the joint and one with ECC in the joint are designed for seismic provisions, but the latter has no transverse reinforcement in the joint. The test programme thereby allows direct comparison of the structural performance of ECC joints with concrete joints for beam–column sub-assemblages for both gravity and seismic design situations. Results show that the use of ECC joints significantly changes the behaviour of the joint from brittle to ductile. Both ECC specimens exhibit superior damage tolerance, with limited shear distortion and multiple fine cracks in the joints, even though no transverse reinforcement is provided in the joint. Moreover, specimens with ECC joints demonstrate improved bond behaviour in early loading cycles.